PENGARUH PENGALAMAN AUDITOR, KOMPETENSI, RISIKO AUDIT, ETIKA, TEKANAN KETAATAN, DAN GENDER TERHADAP KETEPATAN PEMBERIAN OPINI AUDITOR DENGAN SKEPTISME PROFESIONAL AUDITOR SEBAGAI VARIABEL INTERVENING - Meiko Eli Suhesti; Zirman -; Rahmiati Idrus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study is to find out the effect of auditor experience, competence, audit risk, ethics, adherence pressure, and gender to the accuracy of auditor's opinion, directly or indirectly, by using auditor professional skepticism as an intervening variable. The research was conducted in KAP Kota Pekanbaru and KAP Medan City. The samples were obtained randomly as many as 79 respondents. The data were analyzed by using Partial Least Square (PLS) techniques with SmartPLS 2.0 M3 versions. The results showed that auditor experience did have a significant relation to the accuracy on giving opinion. Secondly, competence did have a significant relation to the accuracy on giving opinion. Third, audit risk did have a significant relation to the accuracy on giving opinion. Fourth, ethics did have a significant relation to the accuracy on giving opinion. Fifth, adherence pressure did have a significant relation to the accuracy on giving opinion. Sixth, gender did have a significant relationship to the accuracy of auditor's opinion. From the indirect test, the result showed that the variable of auditor’s professional skepticism was able to strengthen the competence relation and situation of the accuracy of auditor’s opinion. In the other hand, the variable of auditor's professional skepticism was not able to strengthen the relationship of ethics and pressure to the accuracy of auditor's opinion.Keywords: Auditor Experience, Audit Risk, Ethics, Adherence Pressure, Auditor Professional Skepticism